PRDM1 promotes the stemness of gastric cancer cells by enhancing the transactivation of Myc - Hai Qin; Manqin Yuan; Yaqin Yuan; Xue Liu; Siye Yi (Translational Oncology)
Objective: The roles of transcriptional factor PR/SET domain 1 (PRDM1) have been revealed in numerous tumor types. However, its effects on gastric cancer progression are still confusing. This study aimed to explore the roles and underlying mechanisms of PRDM1 in gastric cancer progression. Methods: In silico analysis was used to analyze gene expression levels, expression correlation, and the relationship with patients’ survivals. Functional experiments, including Western blot, RT-qPCR, sphere-formation ability, cytometry analysis, and tumorigenic analysis, were conducted to evaluate PRDM1’s effects on gastric cancer stemness. ChIP, luciferase reporter, and bioinformatic analysis were performed to reveal the underlying mechanisms. Results: we demonstrated that PRDM1 was highly expressed in gastric cancer tissues and cells. Knockdown of PRDM1 significantly attenuated gastric cancer stemness. Mechanistical studies indicated that PRDM1 directly bound to the promoter region of Myc, a critical contributor of cancer stem cells (CSCs), and thus enhanced Myc transcription activity. Conclusions: Taken together, this study indicates that PRDM1 could enhance gastric cancer stemness by increasing the transcriptional activity.